Estetica e significazione. Sul rapporto fra linguaggio ed esperienza sensibile (Lebenswelt. Aesthetics and philosophy of experience., 2023)
Is language an evolutionarily independent faculty from other cognitive capacities? In recent years  two opposing views have clashed: the innatist view, of which linguist and philosopher Noam Chomsky is the main exponent, which answers in the affirmative; the constructivist-empiricist one according to which, on the other hand, language is but the ultimate evolution-complication of non-linguistic capabilities already present in non-human animals.This paper presents and comments on the position of the scientist and philosopher Giorgio Prodi (1928-1987) who avoids this contraposition by thematising an original aesthetic area that would be at the origin of both animal and then human cognition as well as properly human language. Unlike the constructivist view, however, for Prodi such an original aesthetic field can only ground language because it is co-extensive with the original space of biosemiosis.Lastly, the theme of co-evolution is analysed, the only evolutionary mechanism capable, according to Prodi, to account for both the similarities and differences of human language compared to the forms of communication of non-human animals and plants.